Analysis of the Influence of Company Size, Profitability, and Solvency on Dividend Policy in Manufacturing Companies in Indonesia - Wijaya, Indra; Ifadhila, Ifadhila; Prayetno, Prayetno; Lukito, Laksono Edhi; Suherman, Ujang (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Dividend policy is one of the most important decisions in a company's financial management, as it is directly related to the interests of shareholders and the continuity of the company's operations. This research is quantitative. It focuses on analyzing the influence of company size, profitability, and solvency on dividend policy in manufacturing companies in Indonesia. The data in this study are secondary data obtained from reports published by the Indonesia Stock Exchange (IDX). The population used in this study consists of manufacturing companies observed during the period from 2020 to 2024. The data analysis technique in this study uses Multiple Linear Regression Analysis with SPSS. The results of this study indicate that company size, profitability, and solvency have a partial and simultaneous significant effect on dividend policy in manufacturing companies in Indonesia. This suggests that a single factor does not determine dividend policy, but rather the result of a comprehensive consideration of a company's capacity (represented by company size), profit-generating ability (profitability), and the soundness of its capital structure (solvency).